Effectiveness of ICD therapy in real clinical practice. The Olomouc ICD Registry - Taborsky, Milos; Skala, Tomas; Fedorco, Marian; Doupal, Vlastimil; Sovova, Ingrid; Jarkovsky, Jiri; Benesova, Klara; Bezdekova, Monika; Vicha, Marek; Danek, Josef; Kautzner, Josef (Biomedical papers, 2023)
Background. Clinical parameters linked to a low benefit of ICD implantation and increased mortality risks are needed for an individualized assessment of potential benefits and risks of ICD implantation. Methods. Analysis of a prospective registry of all patients hospitalized from 2009 to 2019 in a single centre for a first implantation of any type of ICD. Results. A total of 2,681 patients were included in the registry. Until the end of follow-up (38.4 ± 29.1 months), 682 (25.4%) patients died. The one-year mortality in all patients, the one-year CV mortality, the three-year mortality in all patients, and the three-year CV mortality were 7.8%, 5.7%, 20.6%, and 14.8%, respectively. There was a statistically significant difference when the subgroups were compared according to the type of cardiomyopathy. No significant difference was found between primary and secondary prevention and between the types of devices. Male gender, age ≥ 75 years, diabetes mellitus, and atrial fibrillation were associated with a significantly increased mortality risk. Conclusion. In an analysis of a long-term follow-up of 2,681 ICD patients, we found no mortality difference between patients with ischemic or non-ischemic cardiomyopathy and in the device type. A higher mortality risk was found in men, patients older than 75 years, diabetics, and those with atrial fibrillation.
Keywords: implantable cardioverter-defibrillator; heart failure; primary prevention; time to shock; appropriate shock; mortality